Upaya Peningkatan Produktivitas Usaha Petani dan Buruh Tani Tanaman Holtikultura Melalui Program Dana Bantuan Khusus Pendidikan Kecakapan Hidup - Gatot Yusuf Effendi; Nani Nuraeni (LPPM UNINUS, 2011)
This activity is an exertion in term of enhancing skills, farmers productivity and improving reading, writing, calculating literacy so that by using these new capabilities, they could enrich certain welfare and quality of life. The two potencies are combineable into a single power used to escalate the farmers’welfare, particularly workers who do not have farming lands. Land lackness is not the only one obstacle gaining productivity. The main factor is absolutely farmers’ willingness on achieving knowledge and skills to contribute value-added for their welfare as well as existing resources optimization around the environment. In this case, the role of third party is a quite noteworthy factor; they sit as a facilitator that connects resources and community needs.